Assessment and Treatment of Negative Symptoms in Schizophrenia-A Regional Perspective - Bitter, Istvan; Mohr, Pavel; Raspopova, Natalia; Szulc, Agata; Samochowiec, Jerzy; Micluia, Ioana Valentina; Skugarevsky, Oleg; Herold, Róbert; Mihaljevic-Peles, Alma; Okribelashvili, Nino; Dragašek, Jozef; Adomaitiene, Virginija; et al. (Frontiers in psychiatry, 2021)
Clinicians and researchers consider that there are a variety of symptoms that constitute negative symptoms in schizophrenia, and they may use different definitions for the same symptoms. These differences are also reflected in a variety of negative symptom rating scales. Both research and clinical work are negatively affected by the lack of consensus regarding the symptoms that constitute negative symptoms in schizophrenia. Leading research groups have investigated ways to reduce heterogeneity in the domain of negative symptoms in schizophrenia; however, little attention has been paid to regional differences in the concepts of negative symptoms in schizophrenia. The objective of this review was to collect and summarize information about the assessment and treatment of negative symptoms of schizophrenia in Central and Eastern Europe (CEE). Nineteen experts from 17 countries in CEE participated in this project. The participants collected information about their countries, including the following: (1) the most important publications about negative symptoms in schizophrenia (irrespective of the time of their publication); (2) the most frequently used negative symptom of schizophrenia in clinical practice; (3) definitions of frequently used negative symptoms; and (4) treatment of negative symptoms in schizophrenia. The participating experts/countries most frequently reported the following five negative symptoms: avolition, blunted affect, alogia, asociality, and anhedonia. Several experts also considered other symptoms as belonging to the negative symptom domain, such as a decrease in energy level and changes in personality. The importance of evaluating the long-term course and the relationship between negative symptoms and other symptom domains was also noted. No noticeable differences were reported in the treatment of negative symptoms compared to currently published guidelines and algorithms. The most frequently reported negative symptoms included those defined by the NIMH-MATRICS consensus statement on negative symptoms and recently endorsed in a guidance paper of the European Psychiatric Association. The main differences in the concepts, names, and definitions of primary negative symptoms, especially those related to personality changes, and to the evaluation of the long-term course and relationship between different symptom domains in CEE compared to the current English language literature deserve the attention of psychiatrists and other professionals in this field.
Keywords: assessment; negative symptoms; review; personality; schizophrenia; treatment; Central and Eastern Europe